Service Learning: Study on the degree of satisfaction of students in primary school - Pilar Folgueiras Bertomeu; Esther Luna González (Universidade Federal de Santa Catarina, 2017)
Service learning (SL) is a pedagogical methodology that engages school and community in a common project. Based on this methodology the article presents the results of a comprehensive descriptive study completed with 93 primary education students in order to analyze the satisfaction they have regarding their participation in SL projects. By adapting a model of satisfaction 4 key dimensions are discussed. The main technique for data analysis is content analysis where we triangulate techniques as well as informants. The data analysis shows a high degree of satisfaction from participating students and opens to discussion the key aspects of SL methodology: reflection, evaluation and participation.